The genus Neoanthrenus Armstrong, 1941 (Coleoptera: Dermestidae: Anthrenini): A new synonym of Anthrenus Geoffroy, 1762 - Kadej, Marcin; Háva, Jiří (Zootaxa, 2013)
A new synonym is proposed for Anthrenus Geoffroy, 1762 (= Neoanthrenus Armstrong, 1941 syn. n.) and the following species are transferred to Anthrenus (Nathrenus): Anthrenus (Nathrenus) armstrongielus replacement name for Neoanthrenus armstrongi Kalík, 1957; Anthrenus (Nathrenus) consobrinus (Háva), 2005 new combination; Anthrenus (Nathrenus) frater Arrow, 1915 return to former combination; Anthrenus (Nathrenus) king (Háva), 2002 new combination; Anthrenus (Nathrenus) macqueeni (Armstrong), 1949 new combination; Anthrenus (Nathrenus) niveosparsus (Armstrong), 1941 new combination; Anthrenus (Nathrenus) ocellifer Blackburn, 1891 return to former combination; Anthrenus (Nathrenus) parallelus (Armstrong), 1941 new combination; and Anthrenus (Nathrenus) svatopluki replacement name for Neoanthrenus bilyi Háva, 2003b.